Internet plus and China industrial system's low-carbon development. (November 2021) - Zhang, Wei; You, Jianmin; Lin, Weiwen
Abstract: The Internet Plus concept has deeply affected the development mode of the industrial system. To achieve a low-carbon transition, it is essential to examine how Internet Plus effects the industrial system's carbon intensity. In the existing literature, few studies focus on the influence of Internet usage on the low-carbon development of industries. Based on the Kaya identity, this study explores the relationship and interaction mechanism between Internet Plus, output structure, energy intensity, carbon density, and carbon intensity involved in industrial systems. Based on threshold and dynamic panel models, the Internet effect on carbon intensity, energy intensity, and carbon density of China's industrial system from 2000 to 2015 is studied empirically. Results indicate that the Internet encourages decreased carbon intensity, energy intensity, and carbon density of China's industrial system to various degrees. Specifically, regarding its contribution, the Internet's reducing effect on energy intensity is obvious, whereas that on carbon density is less notable. Further, different threshold effects of the Internet are exerted on carbon intensity, energy intensity, and carbon density. Highlights: Internet encourages carbon intensity decrease. Internet encourages carbon density decrease less notable. Internet encourages energy intensity obviously. There exist different threshold effects on CI, CD, and EI.